The Effect of Biofertilizer on Growth and Yield of Lowland Rice at Alluvial Soil - Pratiwi, Gagad Restu; Nurrahma, Arinal Haq Izzawati; Pratiwi, Etty; Yuniarti, Erny; Ikhwani, Ikhwani (Universitas Sebelas Maret, 2023)
The objective of this study was to investigate the impact of combining different doses and application methods of biofertilizers on the growth and yield of lowland rice (Oryza sativa L.) in West Java. The experiment was designed as a completely randomized factorial with two factors and three replications. The first factor included three different biofertilizer application methods, and the second factor consisted of five different biofertilizer doses. The use of high-fertility alluvial soil was favorable for rice growth when treated with biofertilizers. The interaction between the applied method and biofertilizer dosage had a significant impact on various growth parameters, such as plant height, tiller number, stem fresh weight (g), stem dry weight (g), leaf dry weight (g), panicle number per plant, filled grain number per plant, unfilled grain number per plant, and total grain weight (g). The application of 300 g per pot biofertilizer dose at planting time resulted in the highest filled grain weight per plant (58.6 g) and total grain weight per plant (65.1 g). However, while biofertilizers significantly enhanced rice plant growth, none of the four biofertilizer dose treatments were significant when compared to the control in any of the three application methods. Optimally dosed biofertilizers, when applied at proper planting time, can serve as an alternative approach to enhance rice growth and yield in alluvial soil. This eco-friendly technology has the potential to be integrated into field management practices.